Analysis of COVID-19 Pandemic Waves in Death Figures of Turkey (Epidemiology, Biostatistics, and Public Health, 2023)
Introduction: The COVID-19 pandemic has resulted in a substantial number of deaths worldwide, making it crucial to conduct a periodical behavior analysis of the COVID-19 death figures. By understanding the trends and patterns in mortality rates, decision-makers can make informed choices on prioritization of interventions to pandemics.Method: Death figures due to COVID-19 between 17 March 2020 and 27 November 2022 were taken into account in this study. Mortality data were analyzed using statistical and graphical methods. Von Bertalanffy’s growth model parameters were estimated for each wave. Then the model performance measures were calculated.Discussion: In this study, the course and change of daily mortality data over time were examined. The data reveal that the COVID-19 pandemic occurred in Turkey as four waves. Von Bertalanffy’s growth model appears to be an explanatory model for all pandemic waves according to the performance measures.Conclusion: It was observed that the COVID-19 pandemic spread in Turkey in four waves. Investigating COVID-19 and similar pandemics using versatile and multidisciplinary methods is of great importance in understanding and predicting the behavior of pandemics.
Keywords: COVID-19; pandemic waves; growth models